Síntese e caraterização de MgxPb(1-x)TiO3 - Nóbrega, Jaldair Araújo e (2015)
We report the investigation of structural, optical and electrical properties of the MgxPb(1- x)TiO3 ceramic system produced by mechanosynthesis. The solid state reaction manufacturing method has been proved to be an efficient alternative to manufacture this type of material. By using Raman spectroscopy techniques it was possible observe the effects induced by pressure, from 0 up to 14 GPa, and by temperature from 10 up to 723 K for the samples with x ranging from 0.2 to 1.0. Complementary characterization techniques were also used, including X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Optical Absorption Spectroscopy and Electrical Impedance. XRD enabled the study of structural changes related to the increase in Mg concentrations. Raman analysis allowed the study of vibrational modes, in particular the transversely optical mode E(1TO) of lower frequency in order to characterize the phase transition from tetragonal-ferroelectric to cubic-paraelectric phases. From these results it was possible to construct a phase diagram that relates Mg concentration, temperature and hydrostatic pressure, yielding determine critical temperature (Tc) and critical pressure (Pc) in which phase transition occurs for each sample. Permittivity dielectric measurements were performed for each material, through which it was possible to compare the effects of Mg ratios in the modification of the values of these properties. Finally, a study of optical absorption as a function of Mg concentration was conducted, evidencing changes in gap energies related to the increase of Mg incorporation. The lowest values, 2.86 and 2.9 eV correspond to samples with concentrations of 0.4 and 0.2, respectively. Thus, from a technological point of view, these characteristics are interesting for applications in devices operating in the microwave region.